2018
DOI: 10.1002/jcp.26893
|View full text |Cite
|
Sign up to set email alerts
|

Modulating calcium‐mediated NFATc1 and mitogen‐activated protein kinase deactivation underlies the inhibitory effects of kavain on osteoclastogenesis and bone resorption

Abstract: Osteoclasts are responsible for bone resorption during the process of bone remodeling. Increased osteoclast numbers and bone resorption activity are the main factors contributing to bone loss-related diseases such as osteoporosis. Therefore, modulating the formation and function of osteoclasts is critical for the effective treatment of osteolysis and osteoporosis. Kavain is the active ingredient extracted from the root of the kava plant, which possesses known anti-inflammatory properties. However, the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Treatment reduced inflammatory cell infiltration within soft tissues and also decreased osteoclastic activity. These results are consistent with those obtained in a model of ovariectomy-induced bone loss where kavain was suggested as a candidate drug for the pharmacological management of osteolytic diseases 15 . Indeed, it has been demonstrated that kavain is able to inhibit receptor activator of nuclear factor‐κB ligand (RANKL)-induced osteoclast differentiation and associated bone resorption 15 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Treatment reduced inflammatory cell infiltration within soft tissues and also decreased osteoclastic activity. These results are consistent with those obtained in a model of ovariectomy-induced bone loss where kavain was suggested as a candidate drug for the pharmacological management of osteolytic diseases 15 . Indeed, it has been demonstrated that kavain is able to inhibit receptor activator of nuclear factor‐κB ligand (RANKL)-induced osteoclast differentiation and associated bone resorption 15 .…”
Section: Discussionsupporting
confidence: 90%
“…The anti-inflammatory properties of kavain and its derivatives in multiple cell types such as macrophages, osteoblasts and even adipocytes are now well described 12,14,15,18 . Interestingly, such effects are mediated by several pathways involved in NFκB activation including ERK/LITAF 13 and peroxisome proliferation–activated receptor γ coactivator α (PGC-1α) 12 leading to the control of other detrimental biological events such as oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone absorption is an essential function of osteoclasts in the body [34,35]. The maintenance of the healthy bone structure, morphology, and bone volume requires the dynamic balance between osteoblasts and osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoclasts are differentiated from monocyte/macrophage lineage, which undergoes sequential stages including preosteoclast formation and cell‐cell fusion, involving a variety of proteins and kinases 23‐25 . Id2 is a member of Id family, which functioned as inhibitor of cell differentiation 26 .…”
Section: Discussionmentioning
confidence: 99%